2013
DOI: 10.2478/s11532-013-0301-9
|View full text |Cite
|
Sign up to set email alerts
|

Flow injection analysis of ethambutol in synthetic urine using a graphite-polyurethane composite electrode as an amperometric detector

Abstract: Abstract:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Shao et al applied a MWCNT modified glassy carbon electrode to the detection of this drug in pharmaceutical formulations with a LOD of 7.6 × 10 −4 mM [ 46 ]. Perantoni et al reported two graphite-based electrodes for the amperometric detection of ETB in pharmaceutical formulations [ 41 ] and in synthetic urine [ 47 ] with detection limits of 0.1 mM and 0.0634 mM, respectively. A biosensor based on the use of silver nanoparticles was developed by Ngece et al, exhibiting a LOD of 7.0 × 10 −4 mM ETB in serum samples [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Shao et al applied a MWCNT modified glassy carbon electrode to the detection of this drug in pharmaceutical formulations with a LOD of 7.6 × 10 −4 mM [ 46 ]. Perantoni et al reported two graphite-based electrodes for the amperometric detection of ETB in pharmaceutical formulations [ 41 ] and in synthetic urine [ 47 ] with detection limits of 0.1 mM and 0.0634 mM, respectively. A biosensor based on the use of silver nanoparticles was developed by Ngece et al, exhibiting a LOD of 7.0 × 10 −4 mM ETB in serum samples [ 40 ].…”
Section: Resultsmentioning
confidence: 99%